Fifty Key Thinkers on Religion. - Kessler, Gary (Taylor & Francis, 2011)
Fifty Key Thinkers on Religion is an accessible guide to the most important and widely studied theorists on religion of the last 300 years. Arranged chronologically, the book explores the lives, works and ideas of key writers across a truly interdisciplinary range, from sociologists to psychologists.